The Art of Living With Chronic Health Conditions. (January 2022) - Miller, Vivian J.; Nahar, Shamsun; Praetorius, Regina; Rivedal, Joshua
Chronic health conditions are often accompanied by depression and a decrease in quality of life. This greatly complicates treatment and affects treatment outcomes. Thus, the purpose of this study was to analyze previously published stories of 10 survivors of chronic diseases and depression, using content analysis, to answer the following question: What can be learned from the experiences of the storytellers bereaved by the burden of chronic health conditions? A trajectory with four phases emerged from the analysis of theses survivors' stories: (1) First Impressions, (2) Turning Point, (3) Resiliency … Limitation as an Opportunity, and (4) Paying It Forward. The explored trajectory represented the different stages of personalized experiences with chronic health conditions from initial diagnosis to completion of treatment. Persons diagnosed with chronic health conditions and co-occurring depression find happiness, joy, and freedom if they have adequate support systems, practice creatively unloading their trials, and make time for the opportunity to assist and be of service to others in similar situations. Implications of this study include that the trajectory identified will be a useful guide for professionals and paraprofessionals including those in health care and mental health care, as well as volunteers, friends, and family in working with persons who have co-occurring depression and chronic diseases.